Efficient Synthesis of N-(Difluoropropenyl)amides/Amines from Fluorinated Olefins under Base Promotion - Li, Yang; Shi, Yi-Ran; Li, Zhi-Bo; Li, Hong; Zhu, Wen-Qing; Fan, Qiang-Wei; Li, Xin-Yue (Synlett, 2024)
N-(Difluoropropenyl)amides/amines are an important class of fluorinated compounds. Here, we report an efficient method for synthesizing these compounds without the use of transition metals. Under simple base-promoted conditions, 3-bromo-3,3-difluoroprop-1-ene reacts with N-methylanilines or N-arylacrylamides, with the elimination of one molecule of HBr, to give the target compound. Another efficient method for synthesizing difluoroalkenes is the reaction of 2-bromo-3,3,3-trifluoroprop-1-ene with indole or its analogues.
Keywords: difluoropropenylamides; base catalysis; fluoroalkenes; dehydrohalogenation; transition-metal-free synthesis; indoles